Becker’s Nevus Syndrome in a Pediatric Female Patient (2016)
ABSTRACT: Becker’s nevus is an epidermal cutaneous hamartoma most commonly appearing in adolescents and more in men than women. Becker’s nevus syndrome is a very rare syndrome with characteristics that include Becker nevus and hypoplasia of ipsilateral breast gland plus skeletal, muscular, or other skin disorders.